Preparation method of fluorinated niobium-titanium-oxygen hollow sphere and application of fluorinated niobium-titanium-oxygen hollow sphere in lithium ion battery
Through fluorination treatment and the preparation of hollow sphere structures, the problem of low conductivity of niobium titanium oxide materials is solved, and its rate performance and cycle stability in lithium-ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411831061.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Niobium titanium oxide materials have low electronic and ionic conductivity, which limits their application in lithium-ion batteries.
The hollow sphere structure was prepared by fluorinating the niobium titanium oxide material and using silica microspheres as templates, which improved the specific surface area and electronic conductivity of the material.
Fluorination treatment significantly improves the electronic conductivity and specific surface area of niobium titanium oxide materials, enhances the rapid deintercalation ability of lithium ions, significantly improves the rate performance, and inhibits the occurrence of interfacial side reactions.
Smart Images

Figure CN119637937A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of secondary lithium ion batteries, and in particular relates to a preparation method of fluorinated niobium-titanium oxide hollow spheres and application thereof in lithium ion batteries. Background Art
[0002] Lithium-ion batteries (LIBs) have become the preferred power source for portable electronic devices and electric vehicles due to their high energy density and long cycle life. Graphite has been widely used due to its low cost and high specific capacity (372 mAh g -1 ) has become a commonly used negative electrode material in commercial secondary lithium-ion batteries. However, graphite exhibits a low operating voltage (0.1V vs Li + / Li), resulting in permanent consumption of lithium and the formation of lithium dendrites on the graphite surface, which may cause safety problems. Among the negative electrode intercalation materials, spinel lithium titanate has a higher working voltage (1.55V vs Li + / Li) ensures safety and a long cycle life. However, the theoretical specific capacity of spinel lithium titanate is relatively low (only 175 mAh g -1 ), poor electrical conductivity, which hinders its practical application.
[0003] In recent years, niobium-based oxides have attracted considerable attention as high-power negative electrode materials for lithium-ion batteries and have the potential to replace lithium titanium spinel. As a typical intercalation negative electrode material, the excellent electrochemical performance of niobium titanate mainly stems from its unique structure, in which niobium (Nb) and titanium (Ti) atoms are located at the center of NbO6 and TiO6 octahedra, respectively, in a disordered arrangement. In addition, NbO6 octahedra and TiO6 octahedra are connected by edges and vertices to form an open tunnel-like gap that can accommodate the transmission of lithium ions. The insertion and extraction of lithium ions are relatively easy, so it has excellent rate performance. Niobium titanate not only has the advantages of conventional lithium titanate materials in terms of cycle stability and long life, but also has the advantages of Ti. 3+ / Ti 4+ , Nb 4+ / Nb 5+ and Nb 3+ / Nb 4+ It has a higher theoretical specific capacity (387.6 mA h g-1) and a working potential similar to that of lithium titanate (1.6 V vs Li + / Li), which can effectively prevent the formation of lithium dendrites and the reduction and decomposition of the electrolyte. Compared with traditional batteries, the safety performance is greatly improved. However, niobium titanium oxide materials also have some problems. The electronic and ionic conductivity of the material is low. Therefore, it is urgent to invent a method that can simultaneously improve the electronic and ionic conductivity of niobium titanium oxide materials. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of low electronic and ionic conductivity of niobium titanium oxide materials, and to provide a method for preparing fluorinated niobium titanium oxide hollow spheres and their application in lithium ion batteries. The method uses hydrofluoric acid to fluorinate niobium titanium oxide materials in a one-step method, and simultaneously removes the spherical silica template by etching, thereby achieving the fluorination of niobium titanium oxide and the preparation of hollow spheres in one step. The hollow sphere structure increases the specific surface area, and the fluorination increases the electronic conductivity of the niobium titanium oxide material, greatly improving the rate performance, and is used in the field of high-power lithium ion batteries.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing fluorinated niobium-titanium oxide hollow spheres, the method comprising:
[0007] Step 1, preparing silica microspheres: 150-300mL of anhydrous ethanol and 20-100mL of deionized water are added to a glass container in sequence; under stirring conditions, 5-20mL of ammonia solution is added dropwise to the above solution, and stirred for 30min to ensure sufficient mixing; under room temperature conditions, 20g of tetraethyl orthosilicate (TEOS) is gradually added to the above mixture, and stirred for 24h under magnetic stirring conditions; the white suspension obtained by stirring is taken out, centrifuged at a speed of 8000-10000r / min for three times, and then transferred to a 65°C oven for drying to obtain silica microspheres;
[0008] Step 2: Prepare niobium-titanium hollow spheres using the prepared silica microspheres as a template: disperse the silica microspheres in anhydrous ethanol; add ammonia water to the dispersed suspension under magnetic stirring and continue stirring for 30 minutes; add 1.02g of tetrabutyl titanate and 1.62g of NbCl5 to the suspension and stir magnetically for 2 hours; transfer the resulting solution to a 100mL Teflon-lined stainless steel autoclave and keep it at 180°C for a period of time; after the autoclave is cooled to room temperature, collect the precipitate by centrifugation to obtain a precursor material; transfer it to a box furnace and calcine it in an air atmosphere to obtain SiO2@TiNb2O7;
[0009] Step 3: Dissolve the above SiO2@TiNb2O7 in a hydrofluoric acid solution (30wt%), stir for 30 minutes, transfer to a polytetrafluoroethylene-lined reactor, and keep warm at 180°C for a period of time. Wash the obtained product with ethanol and deionized water for multiple times to remove impurities. Place the sample in a vacuum drying oven at 60°C and dry it for 12 hours to obtain a fluorinated niobium titanium oxide hollow sphere material.
[0010] Furthermore, in step 2, the amount of silica microspheres and ammonia water added is 40-60 mg: 0.5-1 mL.
[0011] Furthermore, in step 2, the Teflon-lined stainless steel autoclave is kept at 180° C. for 12-36 hours.
[0012] Furthermore, in step 2, the calcination temperature of the box furnace is 800-1600°C, and more preferably, the calcination temperature is 800°C, 850°C, or 1000°C.
[0013] Furthermore, in step 2, the calcination time of the box furnace is 6-24 hours.
[0014] Furthermore, in step three, the polytetrafluoroethylene-lined reactor is kept at 180° C. for 6-14 hours.
[0015] The invention discloses an application of fluorinated niobium titanium oxide hollow spheres prepared by the above preparation method as negative electrode materials in lithium ion batteries, wherein the negative electrode of the lithium ion battery is fluorinated niobium titanium oxide hollow sphere material; the fluorinated niobium titanium oxide hollow sphere material, a conductive agent and a binder are dispersed in an NMP solvent in a mass ratio of 96%:2%:2% to obtain a negative electrode slurry, the slurry is coated on a negative electrode current collector, dried, rolled and punched to obtain a negative electrode sheet, and then a button battery is assembled.
[0016] Compared with the prior art, the present invention has the following beneficial effects: in the present invention, the fluorination of niobium titanium oxide and the preparation of hollow spheres are achieved by a one-step method; the hollow sphere structure increases the specific surface area, can withstand a larger real current density, and is conducive to the rapid deintercalation of lithium ions; and fluorination increases the electronic conductivity of the niobium titanium oxide material, greatly improving the rate performance; and fluorination can passivate the electrode surface, inhibit the occurrence of interfacial side reactions, and inhibit gas production; the preparation method can be used in the field of high-power niobium titanium oxide lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the prepared fluorinated niobium titanium oxide hollow sphere;
[0018] Figure 2 This is the SEM image of the prepared fluorinated niobium titanium oxide hollow sphere;
[0019] Figure 3 The fluorinated niobium titanium oxide hollow spheres prepared in Example 1 and the comparative example sample 1C cycle diagram;
[0020] Figure 4 It is a rate performance diagram of the fluorinated niobium titanium oxide hollow sphere prepared in Example 1 and the comparative example sample;
[0021] Figure 5 This is a cycle diagram of the fluorinated niobium titanium oxide hollow spheres prepared in Example 1 and the comparative example sample at 10C. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the concept and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0023] Example 1
[0024] A method for preparing fluorinated niobium-titanium oxide hollow spheres and application thereof in lithium-ion batteries comprises the following steps:
[0025] Step 1: Add 200mL of anhydrous ethanol and 50mL of deionized water to a beaker in sequence. Next, under stirring, add 6mL of ammonia solution to the above solution and stir for 30 minutes to ensure sufficient mixing. Then, at room temperature, gradually add 20g of tetraethyl silicate (TEOS) to the above mixture and continue stirring for 24 hours under magnetic stirring. Subsequently, take out the white suspension obtained by stirring, centrifuge it three times at a speed of 8000-10000r / min, and then transfer it to a 65°C oven for drying to obtain silica microspheres.
[0026] Step 2: Prepare niobium titanium oxide hollow spheres using the prepared silica microspheres as templates: Weigh 50 mg of silica microspheres and disperse them in anhydrous ethanol. Add 0.8 mL of NH3·H2O to the above-dispersed suspension under magnetic stirring and continue stirring for 30 min. Add 1.02 g of tetrabutyl titanate and 1.62 g of NbCl5 to the above suspension and stir magnetically for 2 h. Then, transfer the resulting solution to a 100 mL Teflon-lined stainless steel autoclave and keep it at 180 ° C for 24 h. After the autoclave is cooled to room temperature, collect the precipitate by centrifugation to obtain the precursor material. Subsequently, transfer it to a box furnace and calcine it at 850 ° C for 12 h in an air atmosphere to obtain SiO2@TiNb2O7.
[0027] Step 3: Dissolve SiO2@TiNb2O7 in hydrofluoric acid (30wt%) solution, stir for 30 minutes, transfer to a polytetrafluoroethylene-lined reactor, keep warm at 180°C for 12 hours, wash the obtained product with ethanol and deionized water for multiple times to remove impurities, place the sample in a vacuum drying oven at 60°C and dry it for 12 hours to obtain fluorinated niobium titanium oxide hollow sphere material.
[0028] Step 4: Disperse the obtained niobium titanium oxide hollow sphere material, conductive agent (acetylene black, carbon nanotubes), and binder (PVDF) in N-methylpyrrolidone solvent in a mass ratio of 96%:2%:2% to obtain negative electrode slurry, planetary stir for 10 hours, apply the slurry on the negative electrode collector, dry, roll and punch to obtain the negative electrode sheet, and then assemble the button battery.
[0029] Example 2
[0030] The difference between this embodiment and embodiment 1 is that in step 1, 60 mL of deionized water is used, so that silica microspheres with larger particle sizes can be obtained, and then niobium titanium oxide materials with a greater hollowness can be obtained, thereby enhancing the specific surface area of the material.
[0031] Example 3
[0032] The preparation of fluorinated hollow niobium titanium oxide material in this embodiment is different from that in Example 1 in that: In step 2: using the prepared silica microspheres as a template, niobium titanium oxide hollow spheres are prepared: first, 50 mg of silica microspheres are weighed and dispersed in anhydrous ethanol. Secondly, 0.8 mL of NH3·H2O is added to the above-dispersed suspension under magnetic stirring, and stirring is continued for 30 min. After that, 1.02 g of tetrabutyl titanate and 1.62 g of NbCl5 are added to the above suspension and magnetically stirred for 2 h. Then, the resulting solution is transferred to a 100 mL Teflon-lined stainless steel autoclave and kept at 180 ° C for 24 h. After the autoclave is cooled to room temperature, the precipitate is collected by centrifugation to obtain a precursor material. Subsequently, it is transferred to a box furnace and calcined at 850 ° C for 6 h in an air atmosphere to obtain SiO2@TiNb2O7.
[0033] Example 4
[0034] The preparation of fluorinated hollow niobium titanium oxide material in this embodiment is different from that in Example 1 in that: In step 2: using the prepared silica microspheres as a template, niobium titanium oxide hollow spheres are prepared: First, 50 mg of silica microspheres are weighed and dispersed in anhydrous ethanol. Secondly, 0.8 mL of NH3·H2O is added to the above-dispersed suspension under magnetic stirring and stirred for 30 min. After that, 1.02 g of tetrabutyl titanate and 1.62 g of NbCl5 are added to the above suspension and magnetically stirred for 2 h. Then, the resulting solution is transferred to a 100 mL Teflon-lined stainless steel autoclave and kept warm at 180 ° C for 12 h. After the autoclave is cooled to room temperature, the precipitate is collected by centrifugation to obtain a precursor material. Subsequently, it is transferred to a box furnace and calcined at 850 ° C for 12 h in an air atmosphere to obtain SiO2@TiNb2O7.
[0035] Comparative Example 1
[0036] The comparative example is a pure phase spherical niobium titanium oxide material without hollow sphere structure design and fluorination surface treatment. The specific preparation method is: 1.02g tetrabutyl titanate and 1.62g NbCl5 are added to 30-50mL ethanol and magnetically stirred for 2h. Then, the resulting solution is transferred to a 100mL Teflon-lined stainless steel autoclave and kept at 180°C for 24h. After the autoclave is cooled to room temperature, the precipitate is collected by centrifugation to obtain a precursor material. Subsequently, it is transferred to a box furnace and calcined at 850°C for 12h in an air atmosphere to obtain pure phase TiNb2O7.
[0037] The fluorinated niobium titanium oxide hollow spheres obtained in Example 1 are used as negative electrode materials for lithium-ion batteries. Figure 3 This is a comparison chart of the cycle of the fluorinated niobium titanium oxide hollow spheres prepared in Example 1 and the comparative sample at 1C. It can be seen that after the improvement, the capacity at 1C rate is improved and the cycle is more stable. This is mainly due to the large specific surface area of the fluorinated niobium titanium oxide hollow spheres and the fluorinated electrode surface, which improves the electrochemical properties of the niobium titanium oxide material.
[0038] The rate performance and 10C high rate cycle performance of the samples prepared in Examples 1-4 and Comparative Examples were tested. Figure 4 , 5 As shown, after modification, the rate performance of the niobium titanium oxide electrode is significantly improved. At 0.2C, 0.5C, 1C, 2C, 5C, 10C, 20C, and 40C, the samples of Examples 1-4 all exhibited rate performance superior to that of the comparative samples, and when the current density returned to 0.5C, the sample of the example exhibited excellent reversibility. In addition, the cycle stability at a high rate of 10C was significantly improved, and the cycle stability of Examples 1-4 was superior to that of the comparative samples. This is mainly attributed to the hollow sphere structure design, which enhances the specific surface area of the niobium titanium oxide material, fully contacts with the electrolyte, shortens the lithium ion transmission distance, and the fluorinated surface enhances electronic conductivity, passivates the electrode / electrolyte interface, and reduces the occurrence of side reactions.
Claims
1. A method for preparing fluorinated niobium-titanium oxide hollow spheres, characterized in that: The method is: Step 1, preparing silica microspheres: 150-300mL of anhydrous ethanol and 20-100mL of deionized water are added to a glass container in sequence; under stirring conditions, 5-20mL of ammonia solution is added dropwise to the above solution, and stirred for 30min to ensure sufficient mixing; under room temperature conditions, 20g of tetraethyl orthosilicate (TEOS) is gradually added to the above mixture, and stirred for 24h under magnetic stirring conditions; the white suspension obtained by stirring is taken out, centrifuged at a speed of 8000-10000r / min for three times, and then transferred to a 65°C oven for drying to obtain silica microspheres; Step 2: Prepare niobium-titanium hollow spheres using the prepared silica microspheres as a template: disperse the silica microspheres in anhydrous ethanol; add ammonia water to the dispersed suspension under magnetic stirring and continue stirring for 30 minutes; add 1.02g of tetrabutyl titanate and 1.62g of NbCl5 to the suspension and stir magnetically for 2 hours; transfer the resulting solution to a Teflon-lined stainless steel autoclave and keep it at 180°C for a period of time; after the autoclave is cooled to room temperature, collect the precipitate by centrifugation to obtain a precursor material; transfer it to a box furnace and calcine it in an air atmosphere to obtain SiO2@TiNb2O7; Step 3: Dissolve the above SiO2@TiNb2O7 in a hydrofluoric acid solution (30wt%), stir for 30 minutes, transfer to a polytetrafluoroethylene-lined reactor, and keep warm at 180°C for a period of time. Wash the obtained product with ethanol and deionized water for multiple times to remove impurities. Place the sample in a vacuum drying oven at 60°C and dry it for 12 hours to obtain a fluorinated niobium titanium oxide hollow sphere material.
2. The method for preparing fluorinated niobium-titanium oxide hollow spheres according to claim 1, characterized in that: In step 2, the amount of silica microspheres and ammonia water added is 40-60 mg: 0.5-1 mL.
3. The method for preparing fluorinated niobium-titanium oxide hollow spheres according to claim 1, characterized in that: In step 2, the Teflon-lined stainless steel autoclave is kept at 180° C. for 12-36 hours.
4. The method for preparing fluorinated niobium-titanium oxide hollow spheres according to claim 1, characterized in that: In step 2, the calcination temperature of the box furnace is 800-1600°C.
5. The method for preparing fluorinated niobium-titanium oxide hollow spheres according to claim 1, characterized in that: In step 2, the calcination time in the box furnace is 6-24 hours.
6. The method for preparing fluorinated niobium-titanium oxide hollow spheres according to claim 1, characterized in that: In step 3, the polytetrafluoroethylene-lined reactor is kept at 180°C for 6-14 hours.
7. Use of the fluorinated niobium titanium oxide hollow spheres prepared by the preparation method according to any one of claims 1 to 6 as negative electrode materials in lithium ion batteries.
Citation Information
Patent Citations
Method for preparing three-dimensional porous titanium niobate oxide through template method, and application thereof in lithium ion battery
CN105552369A
Preparation of magnesium fluoride nanocrystal and nitrogen-doped graphene-like hollow nanosphere and application of magnesium fluoride nanocrystal and nitrogen-doped graphene-like hollow nanosphere in lithium metal battery
CN114678496A
Fabrication of uniform titania hollow using silica / titania core / shell nanoparticles
KR1020130070317A
Anode active material, preparing method of the same, lithium ion secondary battery including the same
KR102214227B1